PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MODERASI - Ariani, Merry Okta; Prastiwi, Dewi (Jurnal Akuntansi AKUNESA, 2020)
This study aims to examine the effect of corporate social responsibility on moderated tax aggressiveness with financial performance. Corporate social responsibility is measured using the natural logarithm of CSR costs, then tax aggressiveness is measured using the effective tax ratio (ETR) for five consecutive years, and financial performance is proxied using return on sales (ROS). The research sample of 23 manufacturing companies listed on the IDX, the sample was selected using purposive sampling technique. The results showed that corporate social responsibility had a negative effect on tax aggressiveness. Then, financial performance which is proxied by return on sales (ROS) is able to moderate the effect of corporate social responsibility on tax aggressiveness.